Involving employee performance in the influence of emotional intelligence and transformational leadership on employee motivation at the South Konawe Revenue Agency - Rasnawati, Rasnawati; Nurwati, Nurwati; Montundu, Yusuf (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
This study aims to analyze the influence of emotional intelligence and transformational leadership on the performance and work motivation of employees at the Regional Revenue Agency of South Konawe Regency, with a total of 61 employees. The method used was SEM-PLS analysis with data collected through questionnaires. The results of the study show that emotional intelligence has a positive and significant effect on employee performance, especially in managing workload, effective communication, and harmonious working relationships. Meanwhile, transformational leadership also improves employee performance through individualized attention, role modeling, motivation, and intellectual stimulation. Emotional intelligence also increased work motivation, but the influence of transformational leadership on work motivation was not significant, suggesting the variability of its effectiveness depending on the specific situation. Employee performance plays a significant role in increasing work motivation, both directly and as a mediator in the relationship of emotional intelligence and transformational leadership to work motivation.